농지은행제도 도입에 관한 연구 - 김홍상 (한국농촌경제연구원, 2004)
The current situation of DDA agricultural negotiation and rice market opening negotiation under the WTO system strongly urges Korean government to open more positively agricultural product market, especially rice market, which will result in the decrease in the profitability of rice industry and the rapid decrease in demand and price of farmland. Rice fields have used most of farmlands and the farmland has been the most important asset of farmers in Korea. Farmland market and farmers' economy shall be thrown into confusion by the sharp decline in farmland demand and price. These changes in farmland price have required to introduce a new farmland management system that is very different from the existing ones. The main purpose of this research is to review the possibilities and prepare action programs for introducing farmland banking system as a new farmland management system and a few policy issues surrounding it. This research shows the reasons why the introduction of farmland banking system is necessary and the main role of farmland banking system, and they can be summarized as follows : (1) Korean government should take a measure to stabilize the farmland market, (2) it should cope with the diverse and increasing demand for farmland to accord the changes in farmland systems(making a partial amendment of the Farmland Law) and to empower and enterprise rural community etc, and (3) it should make the rice industry competitive by improving the existing farmsize through ‘farmsize increasing projects’ and restructuring the industry etc. Japanese, French, and American experiences show severe problems of sudden decrease in price and confusion of farmland market. But it will not happen and the decrease of farmland price can play positive role in restructuring rice industry if Korean government takes measures to meet the situation of opening rice market and farmland banking system is introduced to Korea and mobilizes the farmland more actively than before. Farmland banking system can be introduced a little more easily by putting the roles of farmland banking system onto the KARICO(Korea Agricultural and Rural Infrastructure Corporation) that has managed the ‘farmsize increasing projects’. There are several policy issues for introducing this kind of new system : types of buying farmland, the priorities in target group of farmland, time to buy farmland, fundraising, taking legal steps for realizing new programs, harmonizing with other programs, reforming the practicing systems of the related policy programs etc. Researchers : Kim Hong-Sang, Kim Kyeong-Duk E-mail Address : hskim@krei.re.kr
Keywords: 농지은행제도; 농지은행